Association between continuity of primary care and preventable hospitalization in adults with asthma: A cohort study - Sangwan Kim; Eunjung Choo; Eun Jin Jang; Nam Kyung Je; Iyn-Hyang Lee (PLoS ONE, 2025)
Objective Hospitalization often indicates deteriorating health, longer treatment times, and higher healthcare costs. This study aimed to investigate associations between continuity of care (COC) and asthma-related hospitalizations using a rigorous methodology. Methods This retrospective cohort study was conducted using national health insurance claims data. The study included adults with a diagnosis of asthma between 2015 and 2016 in a primary care setting. The exposure was measured using continuity of care indices (COCIs) during the first two years after inclusion. Cohorts were categorized into two groups based on COCI levels. The primary outcome was the incidence of asthma-related hospitalizations, and the secondary outcomes were emergency department (ED) utilization, systemic corticosteroid use, and asthma-related medical costs. Results A total of 24,173 patients were eligible for analysis, 13,212 of whom were continuously cared for by primary doctors (the continuity group), and 10,961 non-continuously (the non-continuity group). During a 2 year-follow-up period, 230 patients (1.74%) were hospitalized in the continuity group and 404 (3.69%) in the non-continuity group. After adjusting for confounding covariates, patients in the non-continuity group were found to be at significantly higher risk of hospital admission (adjusted hazard ratio (aHR)=2.04 [95% confidence interval = 1.73 ~ 2.41]). In addition, the risk of ED visits, systemic corticosteroid use, and costs were higher for patients in the non-continuity group (aHR = 2.26 [1.32 ~ 3.87], adjusted OR=1.58 [1.35 ~ 1.82], and expβ = 1.41 [1.37 ~ 1.45], respectively). Conclusions In adult asthma patients at the early stages of illness, increased continuity of primary care was found to be associated with fewer hospitalizations, fewer ED visits, and lower healthcare expenditures.